Patient Delay and Stage of Diagnosis among Breast Cancer in Bangladesh - Murshed, SM Munawar; Hossain, Syed; Patwary, Devasish; Roy, Ronoda Prosad; Hussain, Syed Akram (Faridpur Medical College Journal, 2021)
Early diagnosis and prompt treatment is the principal goal of physicians dealing with breast cancer. In breast cancer care there are several causes of delay. Delay in diagnosis may be either patient or health provider originated. Besides there are no effective surveillance system, no nationwide active campaign for early diagnosis and screening. Hence delay in diagnosis is not unlikely. The study was done in a Cross sectional setting during January to December 2009 at the Department of Oncology of Bangabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital, National Institute of Cancer Research & Hospital. A total 106 breast cancer patients were recruited for the study from the mentioned study places. Our data suggests on average 40 days delay from development of first symptom to attending traditional or unqualified provider. Time taken in transition from unqualified provider to qualified medical personnel was around another month. The time taken by medical personnel to establish the diagnosis through histopathology was around another 12.5 ±7.0 days, thereafter to perform surgery after diagnosis it took 17.8 ± 18.1 days. After surgery another 31.05±33.8 days were needed to start adjuvant chemotherapy or radiotherapy. Mean total time lapsed from appearance of symptom to perform surgery among breast cancer patients was 114.3±53.2 days with a median delay of 117.5 days. Mean total time lapsed from appearance of symptom to have chemotherapy or radiotherapy among breast cancer patients was 151.2±62.8 days with a median delay of 124 days. Regarding the cause of delay, in 53.8% cases, delay was resulted due to lack of awareness, in 38.9% cases delay was due to lack of money for treatment, in 7.5% case delay was due to the attempt to rely on alternative medicine, in 14.2% cases patients were reluctant, in 18% cases delay was due to problem in diagnosis. In 13.2% cases physician was treating the patient for other reason, in 36% cases patient herself made the delay for fear of consequences of disease or treatment and in 22% cases delay occurred due to long waiting period for surgery. In most cases delay resulted from multiple reasons. Patients with stages III & IV were found to have significantly more total delay than stage I & II diseases (p<.05). Patients with higher educated level made less delay than lower educated level. In conclusion, most important delay is caused by patient's own criteria and negligence. Awareness raising campaign may play an important role in reduction of the delay. Faridpur Med. Coll. J. 2021;16(1):12-16